Congenital Absence of the Common Bile Duct - A Rare Anomaly with an Evolving Association with Esophageal Atresia - Adham Elmously; Saurabh Saluja; Daniel Rosenbaum; Cheguevara Afaneh; Karim Halazun; Nitsana A. Spigland (Elsevier, 2018)
Congenital absence of the common bile duct (CBD), also known as âcholecystohepatic ductâ or âinterposition of the gallbladderâ is a rare extrahepatic biliary anomaly characterized by the hepatic ducts entering the gallbladder directly and the cystic duct draining the entire biliary tree into the duodenum. There have been only been four reports of children with congenital absence of the CBD, with three of these also carrying a diagnosis of esophageal atresia, suggesting an association between the two entities. We report an additional case of a child with a history of tracheoesophageal fistula and congenital absence of the CBD as well a review of the literature. Keywords: Gallbladder interposition, Biliary tract anomaly, Pediatric cholecystitis, Acalculous cholecystitis, Roux-en-y hepaticojejunostomy